Increase on environmental seasonality through the European Early Pleistocene inferred from dental enamel hypoplasia - Darío Fidalgo; Antonio Rosas; Saverio Bartolini-Lucenti; Jean-Renaud Boisserie; Luca Pandolfi; Bienvenido Martínez-Navarro; Paul Palmqvist; Lorenzo Rook; Joan Madurell-Malapeira (Scientific Reports, 2023)
Abstract An in-depth study of the Early Pleistocene European remains of Hippopotamus has allowed the first detailed description of the incidence and types of dental alterations related to palaeopathologies and potentially linked to climatic and environmental factors. The results of a long-term qualitative and quantitative assessment highlight the importance of nutrient deficiencies on the development of dental enamel hypoplasia in Hippopotamus. Glacial cyclicity and the resulting changes in humidity and plant community structure conditioned the local environments critical for the survival of this taxon. Two main intervals of putative constrained nutritionally restrictions were detected at ca. 1.8 Ma and ca. 0.86 Ma (i.e., MIS63 and MIS21, respectively). Statistical comparisons show an increase in the frequency of dental hypoplasia between these two chronological periods, thus reinforcing the idea of increased seasonality in the circum-Mediterranean environments during the Early Pleistocene.